Proximity Bias Following Affective Metaphors in Patients With Depression—Psychoanalytic Considerations - Biran, Iftah; Tripto, Assaf; Arbel, Anat (Frontiers in Psychology, 2019)
Background: Many languages use spatial metaphors to describes affective states such as an upward bias to denote positive mood and a downward bias to denote negative mood, a body proximity bias to denote personal relatedness concern, and right-left bias to denote negative or positive valence. These biases might be related to experiential traces related to these affective states. If this is the case, depressed subjects would show either a downward spatial bias, a body proximity bias or a right-left shift in attention. We evaluated the occurrence of such biases in subjects with depression compared to healthy controls. Methods: Subjects: 10 subjects with depression (5F:5M;age-47.2±15.2) and 10 healthy controls (5F:5M;age=45.8±14.5). Experimental task: Line Bisection task. Lines were presented in 3 spatial orientations (vertical [up-down], horizontal [right-left], radial [proximal-distal]) and were either blank, composed with words (negative/positive/neutral) or with smileys (negative/positive/neutral). There were 21 line types and each was presented 8 times, reaching a total of 168 lines. Results: Compared with healthy controls subjects with depression bisected radial lines significantly closer to their body. There were no significant differences for either horizontal or vertical lines. Conclusion: The proximity spatial bias observed in subjects with depression suggests that depression might activate neural spatial networks. We argue that these networks could be dynamically activated through narcissistic mechanisms as implied in "Mourning and Melancholia" where Freud postulates a narcissistic mediated bias in depression according to which the depressed withdraws from the outside world.